Liver transplantation for hepatocellular carcinoma comparing the Milan, UCSF, and Asan criteria: long‐term follow‐up of a Western single institutional experience. (23rd March 2015) - Bonadio, Italo; Colle, Isabelle; Geerts, Anja; Smeets, Peter; Berardi, Giammauro; Praet, Marleen; Rogiers, Xavier; de Hemptinne, Bernard; Van Vlierberghe, Hans; Troisi, Roberto I.
Abstract Background In patients with hepatocellular carcinoma (HCC), the outcome after liver transplantation (LT) is excellent if tumor characteristics are within the Milan criteria (MC). Expanded Asan criteria (AC) have not yet been validated in Western countries. Methods A total of 76 patients with HCC underwent LT. Patients were divided and compared according to Milan, UCSF, and Asan criteria. Differences between pre‐ and post‐operative assessment were evaluated. Overall survival (OS) and disease‐free survival (DFS) were compared between groups. Predictors of recurrence were investigated. Results Asan criteria provided 26% and 15% more criteria‐fitting patients than MC and UCSF pre‐operatively while 49% and 35% at pathological evaluation. Discrepancy between pre‐ and post‐operative evaluation was 32% for MC, 33% for UCSF, and 18% for AC (p = 0.06). After a median follow‐up of 70.5 months, patients exceeding MC but fulfilling Asan had comparable 5‐yr OS and DFS to patients fulfilling MC (p = 0.17; p = 0.29). Patients exceeding UCSF but fulfilling AC had comparable 5‐yr OS and DFS to patients fulfilling UCSF (p = 0.26; p = 0.32). Number of nodules, macro‐vascular invasion, capsular invasion, and exceeding AC predicted recurrence at multivariate analysis (p = 0.01, 0.03, 0.01, 0.02, respectively). Conclusions The extension to AC allows increasing the number of patients eligible for LT without affecting OS and DFS.